Existence of solution for elliptic equations with supercritical Trudinger–Moser growth. Issue 2 (April 2022) - Faria, Luiz F. O.; Montenegro, Marcelo
Abstract : This paper is concerned with the existence of solutions for a class of elliptic equations on the unit ball with zero Dirichlet boundary condition. The nonlinearity is supercritical in the sense of Trudinger–Moser. Using a suitable approximating scheme we obtain the existence of at least one positive solution.